HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN KOMPETENSI KEPRIBADIAN GURU - Ahmad Razak; Novita Maulidya Jalal (Jurnal Psikologi TALENTA, 2018)
This study examines the relationship between emotional intelligence and personality competence. The subjects of this study were 60 teachers of SMAN 1 Sungguminasa using total sampling techniques. Data retrieval used by using The emotional intelligence scale and personality competency scale. The data was  then processed using parametric statistics, namely Pearson product moment. The results of the analysis show that there is a relationship between emotional intelligence and personality competence. This shows that there is a positive relationship between emotional intelligence and personality competence. The higher the emotional intelligence, the higher the personality competence.